EVALUATION OF POST-EMERGENCE HERBICIDE COMBINATIONS FOR WEED CONTROL, EFFICIENCY, WEED INDEX, AND YIELD IN DIRECT-SEEDED RICE (ORYZA SATIVA L.) (International Journal of Food and Nutritional Sciences, 2023)
Direct-seeded rice (DSR) has gained popularity as a cost-effective and labor-saving alternative to traditional transplanting methods. However, weeds pose a significant challenge to DSR productivity. A field experiment was conducted in a Randomized Block Design (RBD) with three replications to evaluate the efficacy of post-emergence herbicides and to assess their impact on weed control, yield, and economic returns. The study comprised ten treatments: T₁: Chlorimuron Ethyl 25% WP @ 37.05 g a.i./ha (PoE), T₂: Bispyribac sodium 20% + pyrazosulfuron 15% WDG @ 52.50 g a.i./ha + Spreadmax @ 0.5 ml/litre (PoE), T₃: Bispyribac sodium 20% + pyrazosulfuron 15% WDG @ 61.25 g a.i./ha + Spreadmax @ 0.5 ml/litre (PoE), T₄: Bispyribac sodium 10% SC @ 25 ml a.i./ha (PoE), T₅: Pyrazosulfuron 10% WP @ 215 g a.i./ha (PoE), T₆: Triafamone 20% + ethoxysulfuron 10% WG @ 66.5 g a.i./ha (PoE), T₇: Penoxsulam 1.02% + cyhalofop-butyl 5.1% OD @ 135 ml a.i./ha (PoE), T₈: Fenoxoprop (PE) fb Halosulfuron (56 fb 67 ml a.i./ha) (PoE), T₉: Hand weeding (20 and 40 DAS), and T₁₀: Untreated control. Among the treatments, T₃ (Bispyribac sodium 20% + pyrazosulfuron 15% WDG @ 61.25 g a.i./ha + Spreadmax @ 0.5 ml/litre) demonstrated superior weed control, enhanced growth parameters, and significantly improved yield, performing on par with T₂ (Bispyribac sodium 20% + pyrazosulfuron 15% WDG @ 52.50 g a.i./ha + Spreadmax @ 0.5 ml/litre). Additionally, T₇ (Penoxsulam 1.02% + cyhalofop-butyl 5.1% OD @ 135 ml a.i./ha) effectively managed Paspalum monspeliensis. The findings emphasize the importance of selecting appropriate herbicides and tailored weed management strategies based on local weed flora and farming conditions for optimizing DSR productivity.